« Au‑delà » de la double absence : nouveaux regards, nouvelles propositions - Constance de Gourcy (Diasporas: Circulations, Migrations, Histoire)
Since the seminal work of Abdelmalek Sayad, a reference to absence has been less and less used in migration studies. This marker of a social link to distance survives only in the narrative of its disappearance due to technological advances in general and digital migration studies in particular, which change lifestyles and transform the relationship with the distant. However, this observation does not apply to the English‑speaking academic field, which has placed absence at the crossroads of multiple research fields. This article presents a review of the main works that structure this field of research and proposes a relational approach to absence as a common basis for mobility beyond inequalities of access.